2007
DOI: 10.1637/7664-060906r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Validated H5 Eurasian Real-Time Reverse Transcriptase–Polymerase Chain Reaction and Its Application in H5N1 Outbreaks in 2005–2006

Abstract: Real time reverse transcriptase (RRT)-polymerase chain reaction (PCR) for the detection of Eurasian H5 avian influenza virus (AIV) isolates was adapted from an existing protocol, optimized, and validated using a number of genetically diverse H5 isolates (n = 51). These included 34 "Asian lineage" H5N1 highly pathogenic avian influenza (HPAI) viruses (2004-2006), plus 12 other H5 isolates from poultry outbreaks and wild birds in the Eastern Hemisphere (1996-2005). All 51 were positive by H5 Eurasian RRT-PCR. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
142
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(142 citation statements)
references
References 5 publications
0
142
0
Order By: Relevance
“…All samples from birds challenged with HPAI viruses were tested using the matrix-gene real-time reverse transcription-polymerase chain reaction (RRT-PCR) assay described by Slomka et al (2007). All samples from birds challenged with NDV were tested using the RRT-PCR assay of Fuller et al (2009) adapted using a homologous probe.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All samples from birds challenged with HPAI viruses were tested using the matrix-gene real-time reverse transcription-polymerase chain reaction (RRT-PCR) assay described by Slomka et al (2007). All samples from birds challenged with NDV were tested using the RRT-PCR assay of Fuller et al (2009) adapted using a homologous probe.…”
Section: Methodsmentioning
confidence: 99%
“…All RRT-PCR tests were performed alongside a series of RNA standards prepared from 10-fold dilutions of the challenge virus stock preparation. According to the test guidelines, any sample with a threshold cycle (Ct) value 35 was considered negative (Spackman et al, 2003;Slomka et al, 2007;Fuller et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Three carcasses were selected by the veterinary service and submitted to the National Reference Centre for Poultry and Rabbit Diseases (NRGK) in Zurich. The suspicious necropsy findings and the subsequent positive M-gene real-time reverse transcriptase PCR ((rtRT-PCR), (Dalessi et al, 2007)) confirmed the detection of AIV, further corroborated by a positive H5 rtRT-PCR (Slomka et al, 2007). For pathotyping and determination of the neuraminidase subtype, organ samples (brain and kidney) were submitted to the Institute of Virology and Immunology (IVI) in Mittelhäusern.…”
Section: Chronology Of the Outbreak And Measuresmentioning
confidence: 93%
“…3. An H5 RRT-PCR that amplifies within the HA2 portion of the H5 gene was as described and validated (Slomka et al, 2007a (Slomka et al, 2007a). Each final reaction volume was 25 ml and included 2 ml extracted RNA, but the ROX reference dye was excluded.…”
Section: Virus Isolationmentioning
confidence: 99%
“…M-gene, H5 and N1 RRT-PCRs are validated methods (Spackman et al, 2002;Payungporn et al, 2006;Slomka et al, 2007a) that have been recommended in the European Union (EU) Diagnostic Manual for AI (EU, 2006). Suspect AI investigations in the EU normally utilize the M-gene RRT-PCR as a generic first-line screening test, and positive AI results are promptly followed by H5 and H7-specific RRT-PCRs to identify NAI (EU, 2006).…”
Section: Introductionmentioning
confidence: 99%